Pengaruh Struktur Keuangan terhadap Manajemen Laba Perusahaan Manufaktur Tahun 2019-2023 - Sadewo, Annisa Rahmadiani; Pratiwi, Azizah Inas; Fatihah, Safanella Fildza; Khoirul Mz, Muhammad Fauzi; Choirunisa, Reza Asti; Nisa, Syafira Enggar Khoirul (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
To change financial statements for certain purposes, such as improving financial image or avoiding tax regulations, companies often use earnings management. The financial structure of a company, including its liquidity, leverage, capital intensity, and size, can affect this earnings management practice. The purpose of this study is to evaluate the relationship between financial structure and earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. This study uses secondary data obtained from the financial statements of companies listed on the IDX; 55 companies out of 171 companies meet certain criteria, and 260 data are obtained from the financial statements of these companies. The results of the study indicate that capital intensity has a negative effect on earnings management in manufacturing companies; liquidity, leverage, and company size do not affect earnings management.